A Proposed Financing Framework for SMEs: Exploring the Case of Sukuk - Zakzouk, Mahmoud; El-Masry, Ahmed A.; Hassan, M. Kabir; Abdelrahman, Abdelrahman Yousri (Journal of King Abdulaziz University: Islamic Economics, 2023)
The purpose of this study is to explore the purported role(s) of employing Ṣukūk as a source of finance in the field of SMEs. This study contributes to the growing stream of SME financing studies by examining "why" and "how" Ṣukūk can be institutionalised as an additional innovative source. The study proposes an empirically-informed SME financing framework using Ṣukūk. To illustrate this, a qualitative approach is adopted using semi-structured interviews and publicly published secondary materials. Distinct from the previous literature and efforts, this study reveals the powerful role of Ṣukūk in financing SMEs, especially in the Organisation of Islamic Cooperation (OIC) developing economies. A multi-faceted financing framework is developed with two distinct SME Ṣukūk: investment Ṣukūk and charitable Ṣukūk. SME Ṣukūk can be institutionalised into a multi-scenario traditional model and a digital model based on the ideology of crowdfunding. SME charitable Ṣukūk can be institutionalised using two different Ṣukūk tools: Waqf and Ihsān.